Genetic diversity in a collection of Italian long storage tomato landraces as revealed by SNP markers array. (4th March 2019) - Tranchida-Lombardo, Valentina; Mercati, Francesco; Avino, Mariano; Punzo, Paola; Fiore, Maria Carola; Poma, Ignazio; Patanè, Cristina; Guarracino, Mario Rosario; Sunseri, Francesco; Tucci, Marina; Grillo, Stefania
Abstract: Tomato ( Solanum lycopersicum L.) is one of the most important crops worldwide. In this study, we used 7720 genome-wide SNPs to characterize the genetic diversity within a tomato germplasm collection enriched with 64 accessions from southern Italy of the so called "da serbo" type i.e. drought-tolerant and long storage landraces. Notwithstanding the relatively small collection area, 1575 (20.4%) polymorphic SNPs, mostly on Chr11, detected considerable levels of genetic variation. Maximum parsimony analysis of genetic distance revealed four main clusters and clearly separated most "da serbo" landraces from the outgroups. One of the clusters grouped the landraces from the Mount Vesuvius area, though no further indications of a geographic-specific structure were found. STRUCTURE analysis confirmed the presence of four genetic groups within the collection, with admixture between them. A survey of non-synonymous SNPs highlighted several mutations in genes related to stress tolerance and fruit maturation/quality. Overall, our results suggest possible exchange of "da serbo" genetic material between southern Italy regions and indicate that the long storage "da serbo" germplasm could be a promising reservoir of peculiar alleles for traits of interest.